Cross-sectional study to compare the biochemical parameters in low normal versus high normal plasma glucose levels in euglycemic individuals - Jhavar, Dharmendra; Kirti, Neha; Vishwakarma, Sumit Kumar; Chandra, Umesh Kumar; Verma, Vinod (International Journal of Advances in Medicine, 2020)
Background: Since a long time ago, the experts have realized that determination of cut-off point for diagnosing diabetes will be revised over time with the lower blood glucose level as the more sensitive diagnosis for detecting the occurring complication and biochemical changes. Methods: This cross sectional study was carried out in the department of medicine, M.G.M. Medical College and M.Y. Hospital Indore from July, 2016 to August, 2017 in 200 individuals and patients having euglycemic status attending General Medicine OPD. Results: In the low and high normal group 2 (2.0%) and 8 (8.0%) were having abnormal total cholesterol (TC) level respectively. The mean total cholesterol in the low normal group was 117.16±26.94mg/dl and it was 154.74±28.38mg/dl in the high normal group. The difference was found to be statistically significant (p value 0.000). In the low and high normal group, 4 (4.0%) and 17 (17.0%) were having abnormal triglyceride (TG) levels respectively. The mean TG levels in the low and high normal group were 96.93±22.64mg/dl and 110.55±32.37mg/dl respectively. The difference was found to be statistically significant (p value 0.001). In the low and high normal group, 6 (6.0%) and 14 (14.0%) patient was having abnormal uric acid levels respectively. The mean uric acid levels in the low and high normal group was 4.88±1.10mg/dl and 5.31±1.31mg/dl respectively. The difference was found to be statistically significant (p value 0.013). Conclusions: Higher levels of Cholesterol and Triglycerides were found more commonly in high normal euglycemic group compared to low normal euglycemic group. Mean cholesterol and mean triglyceride levels were higher in high normal euglycemic group.